Realizing Constitutional Social Rights Through Judicial Protection - Rodolfo Arango (My University, 2016)
The central thesis of this paper is that we have not been able to argue adequately in favor of the concept of constitutional social rights, because a concept of rights has yet to be developed. Such a concept of rights will be presented here, in the aim to help judges to recognize when constitutional social rights have been violated through state inaction, and to give them judicial protection. This concept is sensitive to human realization, for it addresses the different capacities and conditions of individuals and avoids seeing natural or social disadvantages as objective limitations to the recognition and enjoyment of rights, as does the liberal tradition.